2002
DOI: 10.1076/phbi.40.6.405.8440
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Identification and Hypoglycaemic Studies of the Butanol Fraction from Gynura procumbens

Abstract: The methanol extract of the leaves of Gynura procumbens was partitioned between chloroform, ethyl acetate and nbutanol. Qualitative HPLC identification of the major flavonoid constituents in the n-butanol fraction and separation of standard mixture of isolated compounds from the n-butanol fraction are given. Blood glucose levels in streptozotocin-induced type 2 diabetic rats were reduced by the administration of 1 g/kg of the n-butanol fraction. The results were compared with glibenclamide used as standard dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 9 publications
(5 reference statements)
1
62
0
Order By: Relevance
“…Caffeic acid and chlorogenic acid have anti-oxidant and anti-cancer activities (review in Korkina 2007), while 3,5-di-Ocaffeoylquinic acid exhibited anti-viral activity (Jiratchariyakul et al 2000). However, the bioactive flavonol-glucosides that were found in the leaves of G. procumbens and associated to anti-diabetic activity (Akowuah et al 2002) were not detected in the root culture. Interestingly, no signals of pyrrolizidine alkaloids which are associated with Gynura species were detected thus suggesting that the compounds were not present or produced at too low levels to be detectable in the adventitious root culture.…”
Section: Metabolite Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Caffeic acid and chlorogenic acid have anti-oxidant and anti-cancer activities (review in Korkina 2007), while 3,5-di-Ocaffeoylquinic acid exhibited anti-viral activity (Jiratchariyakul et al 2000). However, the bioactive flavonol-glucosides that were found in the leaves of G. procumbens and associated to anti-diabetic activity (Akowuah et al 2002) were not detected in the root culture. Interestingly, no signals of pyrrolizidine alkaloids which are associated with Gynura species were detected thus suggesting that the compounds were not present or produced at too low levels to be detectable in the adventitious root culture.…”
Section: Metabolite Analysismentioning
confidence: 99%
“…Zhang and Tan (2000) discovered that leaf extracts of G. procumbens significantly suppressed the level of elevated serum glucose, and reduced serum cholesterol and triglyceride levels in diabetic rats. Akowuah et al (2002) and Hassan et al (2010) showed significant hypoglycaemic effect of G. procumbens leaf extracts in streptozotocin-induced diabetic rats. In addition, Akowuah et al (2002) isolated flavonol glycosides (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water and alcohol were primarily selected as the extraction solvents since both are more innocuous (in comparison with other solvents) and commonly used in the food industry. Nev-ertheless, methanol was also used as extractor solvent in this work, since previous studies reported better extraction rates for several bioactive compounds in this type of extracts (Bae et al, 2012;Cau-nii et al, 2012;Akowuah et al, 2002).…”
Section: Bioactive Compoundsmentioning
confidence: 99%